Supervisi Akademik sebagai Strategi Penguatan Kompetensi Guru Dalam Pembelajaran Kolaboratif - Susanto, Ahsanul Huda; Sutopo, Anam; Wulandari, Murfiah Dewi; Minsih, Minsih (Jayapangus Press, 2025)
Collaborative learning is important because it can enhance student engagement and support the development of critical thinking skills. However, to implement it effectively, teachers require guidance in designing and executing these teaching strategies. This study aims to explore the role of academic supervision in strengthening teachers' competencies in collaborative learning at SD Negeri 03 Wukirsawit. The study employs a qualitative approach with data collection techniques through observation, in-depth interviews with teachers, and document analysis. The findings show that academic supervision conducted systematically and continuously has a positive impact on teachers' competencies. Teachers reported an improvement in their ability to design more interactive learning activities that support collaboration among students. Additionally, academic supervision also promotes reflective guidance, helping teachers address challenges in implementing collaborative learning. Another positive impact is seen in the higher student engagement in group activities, leading to a better understanding of the material. This study concludes that academic supervision plays a crucial role in strengthening teachers' competencies and enhancing the quality of collaborative learning. Through structured and continuous supervision, teachers are able to design and implement more effective lessons, which ultimately improve student learning outcomes.